THE INTERDISCIPLINARY RELATIONS OF FORENSIC MEDICINE WITH OTHER SCIENCES - Haydarova Nargizaxon Axtamjon kizi (Ta’lim innovatsiyasi va integratsiyasi, 2025)
Abstract Forensic medicine, also known as legal medicine, is a multidisciplinary science that serves the legal system by applying medical knowledge to criminal and civil law. Its integration with various scientific disciplines ensures the accuracy, objectivity, and effectiveness of investigations and legal proceedings. This paper explores the interrelationship between forensic medicine and other sciences such as pathology, toxicology, genetics, psychology, criminology, and law. Understanding these connections enhances the capabilities of forensic experts and contributes to justice.